1999
DOI: 10.1038/sj.onc.1202546
|View full text |Cite
|
Sign up to set email alerts
|

c-Myc and E1A induced cellular sensitivity to activated NK cells involves cytotoxic granules as death effectors

Abstract: The contact of natural killer (NK) cells with foreign cells and with certain virus-infected or tumor cells triggers the cytolytic machinery of NK cells. This triggering leads to exocytosis of the cytotoxic NK cell granules. The oncoproteins c-Myc and E1A render cells vulnerable to NK cell mediated cytolysis yet the mechanisms of sensitization are not well understood. In a model where foreign cells (rat ®broblasts) were cocultured with human IL-2 activated NK cells, we observed that NK cells were capable of e c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
3
8
0
Order By: Relevance
“…Therefore, c-myc expression during apoptosis could be required for the transcription of specific cell surface proteins required for phagocyte recognition, and it has been shown elsewhere that RNA synthesis still occurs during late-stage apoptosis (30). In agreement with this, it has been shown previously that c-Myc-overexpressing fibroblasts are more sensitive to the cytotoxic effects of natural killer cell-derived granules, and in coculture experiments natural killer cells were able to efficiently destroy only target cells which overexpressed cMyc (32).…”
Section: Discussionsupporting
confidence: 67%
“…Therefore, c-myc expression during apoptosis could be required for the transcription of specific cell surface proteins required for phagocyte recognition, and it has been shown elsewhere that RNA synthesis still occurs during late-stage apoptosis (30). In agreement with this, it has been shown previously that c-Myc-overexpressing fibroblasts are more sensitive to the cytotoxic effects of natural killer cell-derived granules, and in coculture experiments natural killer cells were able to efficiently destroy only target cells which overexpressed cMyc (32).…”
Section: Discussionsupporting
confidence: 67%
“…45). The E1A gene product of adenovirus sensitizes infected cells to NK cell killing (46,47), further supporting the hypothesis discussed above that a role for the E3 complex may be to compensate for the increased sensitivity of infected cells to apoptosis induced by other viral genes. Taken together, these data indicate that the inhibition of TRAIL killing by E3-10.4K/14.5K/6.7K may be critical for adenovirus to evade several host cytotoxic effector mechanisms in vivo.…”
Section: Discussionsupporting
confidence: 57%
“…It was then suggested that this anti-apoptotic action of NF-kB might be mediated by inducing unknown genes responsible for prevention of cell death (Beg and Baltimore, 1996;Wang et al, 1996). However, it is also noted that some genes that are induced by NF-kB, such as p53, Fas ligand and c-Myc, have been implicated in apoptosis (Klefstrom et al, 1997;Siebenlist et al, 1995). Therefore, anti-apoptotic actions of NF-kB may not necessarily require its transcriptional activity.…”
Section: Discussionmentioning
confidence: 99%